2017
DOI: 10.1186/s12872-017-0525-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes mimicking acute coronary syndrome in a large intracranial tumour: A diagnostic dilemma

Abstract: BackgroundST elevation Myocardial infarction is a medical emergency. A variety of noncardiac conditions had been known to mimic the ECG changes that are seen in acute coronary syndrome. Although the common ECG changes that are documented with raised intracranial pressure are T inversions, prolongation of QT interval and sinus bradycardia, ST elevation or depression, arrhythmias and prominent U waves have also been recognized. However, ST elevations in association with primary intracranial tumours are rarely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…reported a case of frontoparietal meningioma where ST elevation in inferior leads prompted management with antiplatelet therapy and unfractionated heparin. [ 9 ] Interestingly, there was no concomitant troponin elevation, and the ECG changes persisted despite the treatment with heparin. This was further complicated by hemorrhage into the tumor and worsening of GCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported a case of frontoparietal meningioma where ST elevation in inferior leads prompted management with antiplatelet therapy and unfractionated heparin. [ 9 ] Interestingly, there was no concomitant troponin elevation, and the ECG changes persisted despite the treatment with heparin. This was further complicated by hemorrhage into the tumor and worsening of GCS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 6 - 8 ] Some of these changes, such as ST-segment elevation/depression, may be indistinguishable from those seen in patients with an acute myocardial ischemic event. [ 1 , 8 , 9 ] Therefore, it is of paramount importance that the clinician is able to distinguish the ECG changes caused by neurological conditions from that of ischemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…NSC is expressed in EKG signs or in left ventricular wall motion abnormalities, the release of a myocardial necrosis enzyme and an increased BNP. In electrocardiography, differences with QT interval prolongation, ST segment depression, long QT syndrome, T-wave inversion and plenty of arrhythmias in NSC have been recognized [9, 10]. In the studies ( n = 32), ST elevation was found in 53.1% of patients with TC whereas ST-depression/negative T with 43.8% [2].…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial pathologies such as hemorrhage, aneurysm, stroke, injury, or a space-occupying lesion, have been reported to cause ECG changes mimicking acute coronary syndrome. [1][2][3] These changes are poorly understood and thought to occur due to altered sympathetic tone and associated catecholamine surge. 2 Though there are reports mentioning the appearance of ECG changes during acute neurological stress, this is an interesting case wherein an American Society of Anesthesiologists (ASA) grade 1 patient with mass effect came for elective surgery developed ECG abnormalities despite her normal physical status and no suggestive history.…”
mentioning
confidence: 99%
“…[1][2][3] These changes are poorly understood and thought to occur due to altered sympathetic tone and associated catecholamine surge. 2 Though there are reports mentioning the appearance of ECG changes during acute neurological stress, this is an interesting case wherein an American Society of Anesthesiologists (ASA) grade 1 patient with mass effect came for elective surgery developed ECG abnormalities despite her normal physical status and no suggestive history. The common reported ECG findings mimic acute coronary syndrome with ST elevation and T inversion with signs and symptoms of neurogenic stunned myocardium such as chest pain, shortness of breath, and hemodynamic instability.…”
mentioning
confidence: 99%